A high-strength and high-conductivity copper alloy wire and its preparation method and application
By adding specific contents of Cr, Fe, Ti, Si elements to the copper alloy wires to form a Cr-rich phase and a Laves Fe2Ti second phase, the shortcomings of existing copper alloy wires in high strength, high conductivity, high temperature and fatigue resistance are solved, and high strength, high conductivity, high temperature and fatigue resistance are realized. It is suitable for pulsed strong magnetic field coils.
Patent Information
- Application Number
- CN202310198006.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-02-24
AI Technical Summary
Existing copper alloy wires have shortcomings in high strength, high conductivity, high temperature resistance and fatigue resistance, which are difficult to meet the needs of pulsed strong magnetic field coils.
The combination of 0.7 to 1.3 wt% Cr, 0.15 to 0.6 wt% Fe, 0.1 to 0.4 wt% Ti, 0.01 to 0.12 wt% Si and Cu were used to form a second phase of Cr-rich phase and Laves Fe2Ti. The composite strengthening of the nano-scale precipitation phase was improved to improve the overall performance of the material.
The tensile strength of 700MPa or more and the conductivity of 65% IACS or more was achieved, and the strength reduction rate was less than 10% after baking at 280°C for 1 hour. It can be continuously lined in fatigue tests with a maximum stress of 700Mpa, a minimum stress of 50MPa, and a cycle cycle of more than 6,000 times.
Smart Images

Figure CN116287847B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of copper alloys, and in particular relates to a high-strength and high-conductivity copper alloy wire and a preparation method and application thereof. Background Art
[0002] The pulse magnet generates a strong magnetic field through the instantaneous high current provided by the pulse power supply. The strong magnetic field itself will produce huge strong magnetic stress to react on the magnet itself, so the coil material is required to have good electrical conductivity and high tensile strength. Because the pulse magnet is repeatedly acted on by strong electromagnetic force under the repeated action of large current, and a large amount of Joule heat is generated at the same time, the coil material is required to have high temperature resistance and fatigue resistance.
[0003] At present, the coil materials mainly adopt the high-strength and high-conductivity CuNb alloy produced in Russia and the CuAg alloy produced in Japan. The processing performance of CuNb alloy is poor and the price is expensive, while Japan restricts the export of high-end CuAg alloy. According to the requirements of magnetic field strength, for lower magnetic field strength, the coil generally adopts an integrated magnet structure, requiring the tensile strength of the coil material to be ≥700MPa and the conductivity to be ≥65%IACS; for high magnetic field strength, a layered reinforcement multi-coil system is generally adopted, in which the tensile strength of the outer coil material is required to be ≥700MPa and the conductivity is ≥65%IACS. At the same time, the coil is required to be baked at 280℃ for 1h, and its strength decreases by no more than 10%, and it is required to be unbroken after 6000 times of repeated stress and strain of 50-700MPa.
[0004] The conductivity and strength of copper alloys are often contradictory. The higher the conductivity, the lower the strength, and the higher the strength, the more difficult it is to improve the conductivity. For example, the maximum tensile strength of C42300 copper alloy can reach 720MPa, but the conductivity is only 30%IACS. Another example is the C70250 alloy, whose tensile strength can reach more than 700MPa, but its conductivity is only about 40%IACS. And alloys like C18150 have a conductivity of more than 80%IACS, but the tensile strength is only about 550MPa, which is difficult to meet the needs of high-strength application scenarios. In service environments such as high current, high load, and strong pulse magnetic field, copper alloys are required to have high strength, high conductivity, high temperature resistance and fatigue resistance. Therefore, it is necessary to develop a copper alloy wire with high strength, high conductivity, high temperature resistance and fatigue resistance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-strength and high-conductivity copper alloy wire and its preparation method and application in view of the shortcomings of the prior art. The copper alloy wire has high strength, high conductivity, high temperature resistance and fatigue resistance, and can be used in pulsed high magnetic field coils.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a high-strength and high-conductivity copper alloy wire, the alloy composition of the copper alloy wire is: 0.7-1.3wt% Cr, 0.15-0.6wt% Fe, 0.1-0.4wt% Ti, 0.01-0.12wt% Si, the balance is Cu and inevitable impurities, the copper alloy wire is mainly composed of Cr-rich phase, Laves Fe 2 Ti second phase two-phase composite strengthening, in which the Cr-rich phase is composed of a Cr-rich second phase with a particle size of 5 to 100 nm and a Cr-rich crystal with a particle size greater than 200 nm. 2 The Ti second phase consists of particles with a particle size of 5 to 100 nm.
[0007] The Cr element added to the high-strength and high-conductivity copper alloy wire of the present invention has a solid solubility of only 0.7wt% in the copper matrix at 1076°C, and its solid solubility decreases rapidly as the temperature decreases. Therefore, the present invention adds Cr to the copper alloy as a precipitation strengthening alloying element. During the casting solidification process, the supersaturated Cr precipitates as crystals; during the aging process, the supersaturated Cr precipitates from the matrix in the form of a second phase, forming a body-centered cubic Cr-rich second phase that is non-coherent with the matrix. Due to the precipitation of the Cr-rich phase, the conductivity of the alloy is also improved. Therefore, the Cr element has an obvious strengthening effect on the copper alloy, while taking into account the conductivity requirements of the copper alloy. In the present invention, it is used as the main alloy strengthening element. However, a simple Cr-rich second phase has poor stability, is prone to aggregation and growth, and produces over-aging, while Fe, Ti, and Si can inhibit the growth of the Cr-rich second phase, and Si forms a Cr-rich phase with excess Cr. 3 The Si phase plays a role in precipitation strengthening, effectively improving the high temperature stability of the material and improving the material's resistance to stress relaxation. When the Cr content is less than 0.7wt%, the strengthening effect of Cr is insufficient and the tensile strength is low; when the Cr content exceeds 1.3wt%, due to the limited solubility of Cr in the copper matrix, its strengthening effect is limited, and the crystals are prone to aggregate and coarsen during solidification. During cyclic stress and strain, the strain is easy to aggregate at the crystals and cause cracks, which is not conducive to the fatigue resistance of the wire. Therefore, in order to have sufficient Cr-rich phase precipitation strengthening and from the perspective of the balance between strength and conductivity, the present invention sets the added Cr content at 0.7-1.3wt%, and adds Fe, Ti, and Si in combination.
[0008] In the copper alloy wire of the present invention, the composite addition of Fe and Ti can form Laves Fe 2 Ti second phase improves the tensile strength and electrical conductivity of the alloy. Due to the low migration rate of Fe and Ti in the copper matrix, the Laves Fe 2The Ti second phase is not easy to coarsen and grow at high temperature, and has good resistance to high temperature softening. When the Fe content is less than 0.15wt%, the Laves Fe 2 The amount of Ti second phase is limited, and the strength of the alloy is insufficient; and when the Fe content is higher than 0.6wt%, the conductivity of the alloy will be reduced. In the copper alloy wire of the present invention, from the perspective of the balance between strength and conductivity, the Fe content is controlled at 0.15-0.6wt%, and the Ti content is controlled at 0.1-0.4wt%. When the Ti content is less than 0.43[Fe], Fe is in excess and the conductivity of the alloy is reduced; when the Ti content is higher than 0.86[Fe]+2.84[Si], excess Ti element will reduce the conductivity of the alloy. Therefore, preferably, the Ti content of the present invention is controlled to satisfy 0.43[Fe]≤[Ti]≤0.86[Fe]+2.84[Si].
[0009] Si can form compounds with elements such as Cr and Ti in copper alloys and precipitate as a strengthening phase. In the copper alloy wire of the present invention, Si is mainly used to balance the excess Ti and Laves Fe 2 Ti second phase composite precipitation, to avoid the alloy conductivity reduction due to excess Ti element. During the solidification process, supersaturated Cr and Si form Cr-rich phase and precipitate as crystals. During the aging process, Si preferentially reacts with excess Ti and Laves Fe 2 Ti second phase complex precipitation, if Si is still surplus, it forms a Cr-rich second phase with Cr. In the copper alloy wire of the present invention, the Si content is controlled at 0.01-0.12wt%, and its content preferably satisfies 0.35([Ti]-0.43[Fe])≤[Si]≤0.35([Ti]-0.43[Fe])+0.067. When the Si content is lower than 0.35([Ti]-0.43[Fe]), it will cause it to be unable to combine with excess Ti, reducing the electrical conductivity of the alloy; when the Si content is higher than 0.35([Ti]-0.43[Fe])+0.067, the Si element is excessive, and it is easy to aggregate with the surplus Cr during the solidification process to form a coarse hard and brittle Cr-rich phase, which is not conducive to improving the plastic deformation and fatigue resistance of the material.
[0010] The copper alloy wire of the present invention is mainly composed of Cr-rich phase, Laves Fe 2 Ti second phase two-phase composite strengthening, in which the Cr-rich phase is composed of a Cr-rich second phase with a particle size of 5 to 100 nm and a Cr-rich crystal with a particle size greater than 200 nm. 2The Ti second phase is composed of particles with a particle size of 5 to 100 nm. The nanoscale precipitated phase can effectively hinder the movement of dislocations and improve the strength of the copper alloy matrix. Obtaining two nanoscale precipitated phases with sufficient number density for composite strengthening is the guarantee for the present invention to obtain a tensile strength of more than 700 MPa. When the number of Cr-rich crystals with a size greater than 200 nm is small and dispersed, its adverse effect on the fatigue performance of the alloy can be ignored. However, when the number of Cr-rich crystals with a size greater than 200 nm is large and aggregated, under the action of cold drawing or cyclic stress and strain, defects are easily accumulated and gathered around the Cr-rich crystal particles, resulting in cracks starting from the crystal particles, causing the alloy wire to break. Therefore, the present invention controls the Cr content and the cooling rate of casting to disperse the Cr-rich crystals with a particle size greater than 200 nm, and in the microstructure on the cross section of the copper alloy wire, its number density is controlled at 0.05 / μm 2 the following.
[0011] The particles constituting the Cr-rich second phase and the particles constituting the Laves Fe 2 The particles of Ti second phase are collectively referred to as second phase particles. In the microstructure on the cross section of the copper alloy wire, the average value of the shortest contour distance between the two second phase particles closest to each other is less than 300nm. When the average value of the shortest contour distance between the two second phase particles closest to each other is less than 300nm, the migration of dislocation lines and subgrain boundaries caused by cyclic stress-strain can be effectively prevented, and the generation of cracks caused by the aggregation and expansion of structural defects caused by repeated fatigue can be effectively prevented. At the same time, recovery recrystallization can be effectively prevented at high temperatures, ensuring that the alloy has good high temperature resistance and fatigue resistance.
[0012] Preferably, the alloy composition of the copper alloy wire of the present invention further includes one or more elements selected from Ni, Zr, Sn, Zn, Ag, and Ce in a total amount of less than 0.5wt%. Among them, Zr, Sn, Zn, and Ag elements can be dissolved in the copper matrix to achieve the effect of solid solution strengthening, thereby improving the strength and fatigue resistance of the alloy; Ni and Ti form Ni during the aging process. 3 The Ti precipitated phase has the effect of precipitation strengthening and reduces the influence of excess Ti on conductivity; the rare earth element Ce has high chemical activity and can effectively remove impurities and purify the copper matrix, reducing the adverse effects of impurity elements on the fatigue resistance and conductivity of the material.
[0013] The copper alloy wire material of the present invention has a tensile strength of more than 700 MPa and a conductivity of more than 65% IACS; after the copper alloy wire material is baked at 280° C. for 1 hour, the strength reduction rate thereof is within 10%; the copper alloy wire material does not break in a fatigue test with a maximum stress of 700 MPa, a minimum stress of 50 MPa, and a cycle number of more than 6000 times.
[0014] The preparation method of the copper alloy wire of the present invention adopts a high-temperature solid solution multi-stage deformation and aging process, and the preparation process includes: melting and casting → extrusion → rough drawing → solid solution → primary cold drawing and primary aging → secondary cold drawing and secondary aging → finished product stretching, wherein the solid solution temperature is controlled at 1000-1050°C, and the cooling rate after solid solution is greater than 200°C / s. Preferably, the total processing rate of the primary cold drawing is controlled at more than 60%, the processing rate of each pass of the primary cold drawing is controlled at 10-30%, the temperature of the primary aging is 400-550°C, and the holding time is 4-10 hours; the total processing rate of the secondary cold drawing is controlled at 40-80%, the processing rate of each pass of the secondary cold drawing is controlled at 10-30%, the temperature of the secondary aging is 300-450°C, and the holding time is 4-10 hours.
[0015] The specific preparation process of the copper alloy wire of the present invention is as follows:
[0016] (1) Melting and Casting
[0017] The ingredients are prepared according to the alloy composition ratio requirements, and the melting and casting can be vacuum melting and casting or continuous casting. When vacuum melting and casting is used, the vacuum degree is required to be ≤10Pa. When continuous casting is used, a covering agent is required to protect to prevent Ti from burning. The melting is carried out at 1200-1400℃, and rapid cooling is used during casting to increase the temperature gradient of solidification, which is conducive to obtaining smaller columnar crystals and makes it easier to evenly disperse Cr-rich crystals.
[0018] (2) Extrusion
[0019] In order to ensure that the coarse precipitated phases precipitated during the casting cooling process are dissolved again and the deformation resistance of the material is reduced, the present invention controls the extrusion temperature of the alloy to 850-950°C and the holding time to 2-4 hours. Under this process, the purpose of homogenizing the alloy structure and reducing the deformation resistance can be achieved. In order to minimize the precipitation of particles during the extrusion process, the present invention preferably uses water seal extrusion.
[0020] (3) Rough drawing
[0021] The processing rate of rough drawing is controlled at more than 70%, which can break up the coarse Cr-rich crystals and facilitate the dissolution of the crystals during subsequent solid solution.
[0022] (4) Solid solution
[0023] In order to achieve full dissolution of the precipitated phase in the extrusion process to increase the supersaturation of the matrix, the solution temperature is controlled between 1000 and 1050°C, and the quenching cooling rate after solution is greater than 200°C / s. The solution treatment allows the precipitated phase in the extrusion process to fully dissolve back into the matrix, and quickly cools to room temperature at a cooling rate greater than 200°C / s to ensure that a supersaturated solid solution is obtained, which is conducive to the uniform precipitation of the second phase during subsequent aging treatment.
[0024] (5) First-stage cold drawing and first-stage aging
[0025] The mobility of Fe and Ti in the copper matrix is low, and a large strain energy is required as the Laves Fe 2 The purpose of cold drawing is to make the Laves Fe 2 The precipitation of Ti second phase provides more strain energy and precipitation channels. Preferably, the total processing rate of primary cold drawing is controlled at more than 60%, and the processing rate of each pass of primary cold drawing is controlled at 10-30%. When the processing rate of primary cold drawing is less than 10%, the shear stress of the drawing die is concentrated on the surface of the wire, a large amount of strain occurs on the surface of the wire, and the center strain is small. Then, during the subsequent aging treatment, the second phase is unevenly distributed from the core to the surface, and the material structure and performance are uneven. When the processing rate exceeds 30%, the pulling force needs to be increased, and the possibility of wire breakage increases. Aging treatment is to achieve Laves Fe 2 The key process of precipitation strengthening of Ti second phase and Cr-rich second phase is that high aging temperature will easily lead to coarsening of second phase, and its strengthening effect is limited, while low aging temperature will lead to insufficient power of second phase precipitation. 2 The Ti second phase and the Cr-rich second phase are fully precipitated. The primary aging temperature of the present invention is preferably 400-550° C. and the holding time is preferably 4-10 hours.
[0026] (6) Secondary cold drawing and secondary aging
[0027] After primary aging, the precipitation power and channels have been exhausted. If the secondary aging treatment is carried out immediately at this time, the strengthening phase cannot be precipitated from the matrix, and the strengthening phase precipitated during the primary aging process will continue to grow, which will reduce the comprehensive performance of the alloy. Therefore, the secondary cold drawing treatment of the alloy after the primary aging treatment is conducive to the redistribution of the precipitated phase, and provides more precipitation channels for the secondary aging treatment. At the same time, the second phase precipitated by the primary aging plays a pinning role on the dislocation generated by the secondary cold drawing deformation, so that the strength of the wire is further improved. When the total processing rate of the secondary cold drawing is lower than 40%, the work hardening effect and the effect of the redistribution of the precipitated phase under the action of shear stress are poor. At the same time, the energy and precipitation channels provided for the secondary aging are too few, which will reduce the strength and conductivity of the alloy. When the total processing rate of the secondary cold drawing is greater than 80%, the alloy is prone to produce cracks and other defects in the hard precipitated phase during the deformation process, splitting the alloy structure and reducing the strength of the alloy. Therefore, the preferred total processing rate of the secondary cold drawing of the present invention is 40-80%, and the processing rate of each pass of the secondary cold drawing is 10-30%. On the one hand, the secondary aging treatment removes residual internal stress and improves the ductility of the alloy. On the other hand, it further promotes the precipitation of the second phase and improves the electrical conductivity and strength of the alloy. When the secondary aging treatment temperature is lower than 300°C, the excessively low temperature only releases the internal stress of the alloy but fails to promote precipitation, thereby reducing the strength and electrical conductivity of the alloy. When the secondary aging treatment temperature is higher than 450°C, the excessively high temperature will cause the existing precipitation strengthening phase to grow rapidly, and the strength of the alloy will be reduced. Therefore, the secondary aging treatment temperature should not be too high. The secondary aging temperature is preferably 300-450°C, and the holding time is preferably 4-10 hours.
[0028] (7) Finished product stretching
[0029] Finished product stretching with a stretching ratio of less than 15% can obtain a smooth material surface and slightly increase the strength of the material without affecting the conductivity of the material.
[0030] Compared with the prior art, the advantages of the present invention are:
[0031] (1) The copper alloy wire of the present invention is mainly composed of Cr-rich phase, Laves Fe 2 Ti second phase two-phase composite strengthening, in which the Cr-rich phase is composed of a Cr-rich second phase with a particle size of 5 to 100 nm and a Cr-rich crystal with a particle size greater than 200 nm. 2 The Ti second phase consists of particles with a particle size of 5 to 100 nm.
[0032] (2) The present invention controls the Cr-rich phase and the Laves Fe phase by designing the alloy composition and adopting two-phase composite strengthening. 2The size of the Ti second phase is controlled, and the distribution of the second phase is further controlled, so as to achieve the excellent comprehensive performance of the alloy, that is, the copper alloy wire has a tensile strength of more than 700MPa and a conductivity of more than 65%IACS; after the copper alloy wire is baked at 280℃ for 1h, its strength reduction rate is within 10%; the copper alloy wire does not break in the fatigue test with a maximum stress of 700Mpa, a minimum stress of 50MPa and a cycle number of more than 6000 times.
[0033] (3) The copper alloy wire of the present invention can be used in pulsed high magnetic field coils. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a transmission electron microscope (TEM) image of the finished alloy wire of Example 1;
[0035] Figure 2 This is a scanning electron microscope (SEM) image of the finished alloy wire of Example 3. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below with reference to the accompanying drawings and comparative examples.
[0037] The copper alloy components of the embodiments and comparative examples shown in Table 1 were prepared and melted at 1200-1400°C; then extruded at 850-950°C for 2-4 hours; then roughly drawn at a processing rate of more than 70%; then solid solution was performed at 1000-1050°C, and after solid solution, cooling was performed at a cooling rate of more than 200°C / s; then primary cold drawing and primary aging were performed, and the total processing rate of the primary cold drawing was controlled to be more than 60%. The processing rate of each pass of the primary cold drawing is controlled at 10-30%, the temperature of the primary aging is 400-550°C, and the insulation time is 4-10 hours; then the secondary cold drawing and secondary aging treatment are carried out, the total processing rate of the secondary cold drawing is controlled at 40-80%, the processing rate of each pass of the secondary cold drawing is controlled at 10-30%, the temperature of the secondary aging is 300-450°C, and the insulation time is 4-10 hours; finally, the finished product is stretched at a finished product elongation rate of less than 15% to obtain a wire sample with a smooth surface.
[0038] The properties of each of the obtained wire rod samples were evaluated under the following conditions.
[0039] The room temperature tensile test was carried out on a precision universal mechanical properties testing machine in accordance with GB / T 228.1-2010 Tensile test of metallic materials Part 1: Room temperature test method. Three wires were selected for the test and the average value was calculated as the tensile strength of each wire.
[0040] The conductivity test is in accordance with "GB / T 3048.2-2007 Electrical performance test methods for wires and cables Part 2: Resistivity test of metallic materials". The testing instrument is a ZFD microcomputer bridge DC resistance tester with a sample length of 500mm.
[0041] For the high temperature resistance test, the wire was placed in a furnace at 280°C for 1 hour and then subjected to a tensile test according to GB / T 228.1-2010. The tensile strength after baking was compared with that before baking, and the percentage of reduction in tensile strength relative to that before baking was calculated.
[0042] The fatigue test is carried out in accordance with "GB / T3075-2021 Axial Force Control Method for Fatigue Test of Metal Materials" using a fatigue testing machine with a maximum stress of 700Mpa and a minimum stress of 50MPa. If the cycle exceeds 6000 times without disconnection, it is judged as qualified (OK), otherwise it is judged as unqualified (NG).
[0043] The particles that make up the Cr-rich second phase and the particles that make up the Laves Fe 2 The particles of Ti second phase are collectively referred to as second phase particles. The shortest contour distance between the two closest second phase particles in the microstructure on the cross section of the copper alloy wire, the number density of Cr-rich crystals, and the particle size were calculated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) and statistical analysis of the images.
[0044] Specifically, regarding the particle size, the area of the second phase particles in the image taken by a transmission electron microscope (TEM) is calculated, and the diameter of a circle equivalent to the area is converted into the size of the particle. Preferably, statistical analysis is performed on any five or more TEM images.
[0045] Regarding the shortest contour distance between the two second-phase particles that are closest to each other, for any target particle selected on the image, the distance between the contour of the particle and the neighboring particle is calculated, and the neighboring particle with the shortest contour distance to the particle is taken as the nearest neighbor particle, and the shortest contour distance between the two is taken as the nearest neighbor distance. The average value of the shortest contour distance is calculated, that is, within the observation range (i.e., the 2μm×2μm range on the wire cross section), 10 target particles (i.e., second-phase particles with a particle size of less than 100nm) are randomly selected, and the nearest neighbor particles of these target particles and the shortest contour distances between these target particles and the nearest neighbor particles are respectively determined, and the average value of the 10 shortest contour distances is taken. Preferably, any 5 or more TEM images are used for the above statistical analysis.
[0046] Regarding the number density of Cr-rich crystals, the target particles (i.e., Cr-rich crystals with a particle size greater than 200 nm) within the observation range (i.e., 42 μm × 56 μm range on the wire cross section) are counted from the images taken by scanning electron microscopy (SEM), and the number of Cr-rich crystals per unit area is obtained by dividing the number by the area of the observation range.
[0047] The transmission electron microscope (TEM) image of the finished alloy wire of Example 1 is shown in Figure 1 The scanning electron microscope (SEM) image of the finished alloy wire of Example 3 is shown in Figure 2 . The composition, organization and performance of each embodiment and comparative example are summarized in Table 1. It can be seen that the copper alloy wire samples of each embodiment of the present invention have achieved tensile strength ≥ 700MPa and electrical conductivity ≥ 65% IACS. The copper alloy wire of the present invention can meet the strength reduction rate of less than 10% after baking at 280°C for 1h, and is not broken in the fatigue test with a maximum stress of 700Mpa, a minimum stress of 50MPa, and a cycle of more than 6000 times. At the same time, it can be found from Comparative Examples 1 to 6 that if the content of alloying elements exceeds the design range of the present invention, it will have different degrees of adverse effects on the strength, conductivity, high temperature resistance and fatigue resistance of the alloy.
[0048]
Claims
1. A high-strength and high-conductivity copper alloy wire, characterized in that: The alloy composition of the copper alloy wire is: 0.7-1.3wt% Cr, 0.15-0.6wt% Fe, 0.1-0.4wt% Ti, 0.01-0.12wt% Si, and the balance is Cu and inevitable impurities. The copper alloy wire is mainly reinforced by a Cr-rich phase and a Laves Fe2Ti second phase, wherein the Cr-rich phase is composed of a Cr-rich second phase with a particle size of 5-100nm and a Cr-rich crystal with a particle size greater than 200nm, and the Laves Fe2Ti second phase is composed of particles with a particle size of 5-100nm.
2. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: The particles constituting the Cr-rich second phase and the particles constituting the Laves Fe2Ti second phase are collectively referred to as second phase particles. In the microstructure on the cross section of the copper alloy wire, the average value of the shortest contour distance between the two closest second phase particles is less than 300 nm.
3. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: In the microstructure of the cross section of the copper alloy wire, the number density of the Cr-rich crystals is 0.05 pieces / μm 2 the following.
4. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: [Ti], [Fe], [Si] represent the Ti content, Fe content and Si content in the alloy composition of the copper alloy wire respectively, then the Ti content satisfies: 0.43[Fe]≤[Ti]≤0.86[Fe]+2.84[Si], and the Si content satisfies: 0.35([Ti]-0.43[Fe])≤[Si]≤0.35([Ti]-0.43[Fe])+0.
067.
5. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: The alloy composition of the copper alloy wire further includes one or more elements selected from Ni, Zr, Sn, Zn, Ag, and Ce in a total amount of less than 0.5 wt %.
6. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: The copper alloy wire has a tensile strength of more than 700MPa and a conductivity of more than 65%IACS; after being baked at 280°C for 1h, the strength reduction rate of the copper alloy wire is within 10%; the copper alloy wire does not break in a fatigue test with a maximum stress of 700MPa, a minimum stress of 50MPa, and a cycle number of more than 6000 times.
7. The method for preparing a high-strength and high-conductivity copper alloy wire according to any one of claims 1 to 6, characterized in that: The high-temperature solid solution multi-stage deformation and aging process is adopted, and the preparation process includes: melting and casting → extrusion → rough drawing → solid solution → primary cold drawing and primary aging → secondary cold drawing and secondary aging → finished product stretching, among which, the solid solution temperature is controlled at 1000~1050℃, and the cooling rate after solid solution is greater than 200℃ / s.
8. The method for preparing a high-strength and high-conductivity copper alloy wire according to claim 7, characterized in that: The total processing rate of the first-level cold drawing is controlled at more than 60%, the processing rate of each pass of the first-level cold drawing is controlled at 10~30%, the temperature of the first-level aging is 400~550℃, and the insulation time is 4~10 hours; the total processing rate of the second-level cold drawing is controlled at 40~80%, the processing rate of each pass of the second-level cold drawing is controlled at 10~30%, the temperature of the second-level aging is 300~450℃, and the insulation time is 4~10 hours.
9. Use of the high-strength and high-conductivity copper alloy wire according to any one of claims 1 to 6 in a pulsed high-magnetic field coil.
Citation Information
Patent Citations
Copper alloy material, and method for production thereof
CN101680056A
Precipitation enhanced type brass alloy and preparation method thereof
CN105002394A